Solar Tracker Design Based on Arduino Nano to Improve Solar Energy Efficiency - Anderias Henukh,; Amzal Heri,; Algiranto,; Merta Simbolon, (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
This research aims to develop and build a solar tracking system or solar tracker utilizing the Arduino Nano microcontroller. The primary purpose of this technology is to improve solar panel efficiency by automatically moving them to follow the sun's movement throughout the day. Solar energy is a renewable energy source that is becoming increasingly popular to address the difficulties of the energy crisis and climate change. However, the effectiveness of solar panels is directly proportional to the amount of sunlight they get. Therefore, designing an Arduino Nano-based solar tracker is an innovative solution to increase solar energy efficiency. This article discusses the design and implementation of an Arduino Nano-based solar tracker to optimize solar energy production by moving solar panels automatically to follow the sun's movement throughout the day. Is known that the use of a solar tracker can increase the output voltage of solar cells up to 17.14% compared to static and the lowest optimization value was obtained at 17.00, namely at a value of 8.82%, as an implication of the geographical position of the research area, which experiences sunset more quickly.